Impact of On-street Parking on Urban Arterial Performance: A Quantitative Study on Travel Speed and Capacity Deterioration - Sugiarto -; Thirayoot Limanoond (Aceh International Journal of Science and Technology, 2013)
Abstract - Traffic congestion has been a serious social and technical problem since the early year’s rapid motorization in Banda Aceh, Aceh Province of Indonesia. Urban arterial performance becomes the crucial concerns of many traffic engineers. Arterial performances were analyzed using oblique cumulative plots and breakdown method. The approaches are time series treatment between cumulative vehicles arrival versus time contracted from data recorded by video cameras. Investigations were conducted during both morning and evening peak hours on three regular weekdays for observing saturation condition in order to observe the maximum capacity under prevailing conditions. This study examined the impact of presence on-street parking on deterioration both travel speed and capacity. It found that capacity diminished slightly 10-13% (275-368vph) compared to the pre-breakdown condition. Likewise, during the breakdown, speed dropped about 13-19% (3-5kph) controlled by pre-breakdown as well. The simulation software so called VISSIM 5.30 was governed to estimate the measurement of effectiveness (MOEs) by removing on-street parking from a site of study. The MOEs reveal that removing on-street parking able to reduce average delay approximately 12 sec/veh (32%) and increase speed about 5kph (24%).    Keywords: Arterial performance, pre-breakdown, breakdown, travel speed, capacity, on-street parking, simulation, VISSIM 5.30, MOEs.